2007
DOI: 10.1098/rsta.2007.2144
|View full text |Cite
|
Sign up to set email alerts
|

Mixed valency in polynuclear Mn II /Mn III , Mn III /Mn IV and Mn II /Mn III /Mn IV clusters: a foundation for high-spin molecules and single-molecule magnets

Abstract: Mixed-valent Mn/O dinuclear and polynuclear molecular compounds containing Mn III are almost without exception trapped valence. Large differences between the strengths of the exchange interactions within Mn II Mn III , Mn III Mn III and Mn III Mn IV pairs lead to situations where Mn III Mn IV interactions, the strongest of the three mentioned and antiferromagnetic in nature, dominate the intramolecular spin alignments in trinuclear and higher nuclearity mixed-valent complexes and often result in molecules that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Likewise, finite class 2 clusters containing Mn(II) and Mn(III), for example, have combinations of ferro-and antiferromagnetic intracluster magnetic exchange, which yield very high spin ground states so that the clusters behave as nano-sized superparamagnets, as described here by Christou (Stamatatos & Christou 2008). When analogous situations are found in infinite lattice oxides, such as perovskites, we find many fascinating phenomena arising from the different distributions of the two oxidation states, coupled with the interaction between localized and delocalized electrons.…”
mentioning
confidence: 99%
“…Likewise, finite class 2 clusters containing Mn(II) and Mn(III), for example, have combinations of ferro-and antiferromagnetic intracluster magnetic exchange, which yield very high spin ground states so that the clusters behave as nano-sized superparamagnets, as described here by Christou (Stamatatos & Christou 2008). When analogous situations are found in infinite lattice oxides, such as perovskites, we find many fascinating phenomena arising from the different distributions of the two oxidation states, coupled with the interaction between localized and delocalized electrons.…”
mentioning
confidence: 99%
“…The room-temperature χ M T value of 7.52 cm 3 Kmol −1 is very close to the theoretical value of 7.375 cm 3 Kmol −1 for two non-interacting Mn II and Mn III ions (g = 2.00) of the 1-D repeating unit. The χ M T product remains almost constant in the 300-100 K range, and upon further cooling, it steadily decreases down to a value of 4.85 cm 3 Kmol −1 at 2 K. The overall magnetic response of 2 is suggestive of the presence of weak antiferromagnetic exchange interactions between the metal ions, as expected for a system where the alternating Mn II and Mn III ions are solely bridged by a syn-anti carboxylate group [38,43].…”
Section: Solid-state Magnetic Susceptibility Studiesmentioning
confidence: 77%
“…The magnetic properties of a different Mn 12 complex were also reported to be affected when the molecule was adsorbed on a gold surface with a self-assembled monolayer [22]. Other studies have further shown that significant structural deformations and changes in the spin centre-spin centre coupling strengths occur when Cr 7 Ni and Mn 6 MMs are adsorbed on gold surfaces [23][24][25]. On the other hand, some experiments have achieved surface-adsorbed MMs with intact magnetic properties.…”
Section: Introductionmentioning
confidence: 96%
“…. can be described by the Ky Fan metric [41], 6) which shows that for any fixed > 0, there exists an integer n 0 such that for all k > n 0 ,…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation